The relationship between organisational justice perceptions, organisational trust and willingness to engage in protest action for higher wages among low-income employees in South Africa - Mbolela, Aura Yombo (Organisational Psychology, 2021)
While common in South Africa, workplace protest actions frequently lead to losses on both sides: productivity losses for organisations and loss of income for protesting employees. It is therefore important to investigate which factors may contribute to low-income workers' decision to protest for higher wages. Based on the theoretical integration of social exchange theory and fairness heuristic theory it was argued that fairer treatment (organisational justice) decreases workers' willingness to engage in protest actions through its positive influence on organisational trust. The researcher examined employees' perceptions of fairness shown by their employer, supervisor and co-workers. A descriptive, cross-sectional research design was employed to test this assumption. Data was collected from low-income employees working in South African factories and retail stores who completed a self-report survey (N = 147). The results of a regression analysis confirmed that employees' perceptions of organisational justice predicted their willingness to engage in protest actions for higher wages when gender and previous involvement in protest actions were kept constant. Perceptions of interpersonal justice as shown by the supervisor was the unique predictor of willingness to engage in protest action, indicating that the decision to protest is not primarily driven by monetary concerns (distributive justice) but rather by how low-income workers feel treated in the workplace. Mediation analysis results revealed that the relationship between organisational justice and willingness to engage in protest action is not through mutual trust. Taken together, this research demonstrated that there is a need for organisations to invest in fairness in the workplace. Most specifically, organisations could focus on training supervisors to treat employees with respect and dignity as it could contribute to employees' decision to refrain from protesting at work.